The Third Republic in France : 1870 - 1940 ; conflicts and continuities - Fortescue, William (Routledge Sources in history, 2000)
"This book provides original sources, detailed commentary and helpful chronologies and bibliographies on: the emergence of the regime and the Paris Commune of 1871; Franco-German relations; the character of the Third Republic and the nature of French Republicanism and Socialism; Church-state relations; anti-Semitism and the Dreyfus Affair; the role of women and the importance of the national birth rate; and the character of the French Right and of French fascism."--BOOK JACKET.